POLIGAMI DI MALAYSIA - Abdullah, Raihanah (Jurnal Syariah, 2019)
Polygamy has been a controversial issue not only in Malaysia but also in all Muslim countries in the world. Thus, a specific provision on polygamy has been enacted in the Islamic Family Law to control polygamy due to the family unstability among the society caused by those who abuse the permission granted by the Quran. This article attempts to discuss the law of polygamy in Malaysia, its problems and the solutions towards controlling polygamy among the Muslim society in Malaysia.